Rare earth ion doped lead-free halide double perovskite material and preparation method thereof

Through rare earth ion-doped lead-free biperovskite materials combined with hydrothermal synthesis process optimization, traditional lead-based perovskite materials have been solved, and efficient up-down conversion luminescence and quantum yield improvements are achieved. They are suitable for multifunctional optoelectronic devices and anti-counterfeiting labels.

CN120137664APending Publication Date: 2025-06-13CHINA JILIANG UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510627001.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-05-15
Publication Date
2025-06-13

AI Technical Summary

Technical Problem

Traditional lead-based perovskite materials have high toxicity and poor stability, while existing lead-free biperovskite materials have problems such as wide bandgap, indirect bandgap, low carrier transmission performance and single light regulation methods.

Method used

By designing lead-free biperovskite materials co-doped with rare earth ions (Yb3+, Nd3+, Er3+), combined with hydrothermal synthesis process optimization, it can achieve efficient up-down conversion luminescence, and improve material stability and quantum yield.

Benefits of technology

The dual-mode luminescence characteristics are achieved, the quantum yield is increased to 29%, the carrier life is long, the defect state density is low, and the material has high stability in normal temperature and humidity environments. It is suitable for anti-counterfeiting labels and optoelectronic device applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120137664A_ABST
    Figure CN120137664A_ABST
Patent Text Reader

Abstract

The invention discloses a rare earth ion doped lead-free halide double perovskite material and a preparation method thereof, the material is rare earth ion # imgabs0 # co-doped # imgabs1 # double perovskite, the material is synthesized through a hydrothermal method, by optimizing the doping proportion and the energy transfer path of rare earth ions, the material respectively shows up-down conversion luminescence characteristics in a visible light region under excitation of 365 nm and 980 nm, and the material has the advantages of high light emitting efficiency, high light emitting efficiency and the like. The quantum yield is as high as 29%, and is obviously superior to that of the existing lead-free perovskite material. The preparation method comprises the steps of raw material proportioning, hydrothermal reaction conditions and application of the anti-counterfeiting mark. The material has the characteristics of no lead, environment friendliness, controllable synthesis, excellent stability and the like, and is suitable for the fields of counterfeiting prevention, photoelectric devices, biological imaging and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of inorganic luminescent materials, and specifically relates to a rare earth ion-doped lead-free halide double perovskite material and a preparation method thereof, as well as applications of the material in anti-counterfeiting labels, optoelectronic devices and biological imaging. Background Art

[0002] In recent years, perovskite materials have become a research hotspot due to their excellent optoelectronic properties. ) have high light absorption coefficient and carrier mobility, but the toxicity and environmental instability of lead elements severely limit their practical applications. To replace lead-based materials, lead-free halide double perovskites (such as , ) was proposed, but it has the following problems: 1. Wide band gap and indirect band gap: resulting in low luminescence efficiency in the visible light region. The quantum yield of existing lead-free double perovskites is generally less than 20%; 2. Poor carrier transport performance: high defect state density, excitons are easily captured, limiting their application in photovoltaic devices; 3. Single light control method: Existing materials are difficult to achieve ultraviolet excitation down-conversion (DC) and near-infrared excitation up-conversion (UC) luminescence at the same time, which limits multifunctional applications.

[0003] In view of the above problems, the present invention designs rare earth ions ( , , ) co-doped lead-free double perovskite , combined with the optimization of the hydrothermal synthesis process, efficient up-and-down conversion luminescence is achieved, and the material stability and quantum yield are significantly improved. Summary of the invention

[0004] The present invention is directed to conventional lead-based perovskite materials (such as ) are highly toxic and have poor stability, and existing lead-free double perovskite materials (such as , ) have wide band gap, indirect band gap, low carrier transport performance, and single light control method. A method based on rare earth ions is proposed. , , Co-doped lead-free halide double perovskite materials (chemical formula: ) and a preparation method thereof.

[0005] The core innovations of the present invention include: (1) Matrix material design: As the matrix, its cubic phase structure (space group Fm-3m, lattice parameter a = 10.68 Å) is highly similar to that of lead-based perovskite ( ), but it completely contains no lead element; The ionic radius of (0.94 Å) is highly matched with that of (0.87 Å), (0.98 Å),

[0006] (2) Rare earth ion cooperative energy transfer mechanism: As a sensitizer, it absorbs near-infrared light at 980 nm and transfers the energy to through transition; As an energy bridge, it further transfers the energy to through transition; As an activator, it realizes multi-wavelength visible light emission through (green light), (green light), (red light) transitions.

[0007] (3) Optimization of doping ratio: The doping concentration is determined through orthogonal experiments ( : 20 mol%, : 1 mol%, : 5 mol%), and the total rare earth doping amount is controlled within 1 - 50 mol% of the site to avoid concentration quenching effect.

[0008] (4) Dual-mode luminescence characteristics: Under 365 nm ultraviolet light excitation, down-converted green light (525 nm, 550 nm) and red light (667 nm) are realized through self-trapped excitons (STE) and energy level transitions; under 980 nm near-infrared light excitation, up-converted visible light emission is realized through multi-step energy transfer, breaking through the limitation of the single luminescence mode of traditional lead-free materials.

[0009] A rare earth ion-doped lead-free halide double perovskite material and its preparation method of the present invention have the following remarkable advantages compared with the prior art: 1. Lead-free environmental protection: Using matrix to replace traditional lead-based perovskite completely eliminates lead toxicity and meets the requirements of green environmental protection.

[0010] 2. Controllable synthesis process: The hydrothermal synthesis conditions are mild (180°C, 12 h), the product has high crystallinity and uniform particle size (200 - 500 nm), and the doping ratio is precisely controllable ( 1 - 30%, 1 - 10%, 1 - 20%).

[0011] 3. Excellent optical properties: Dual - mode luminescence: Under 365 nm excitation, down - converted green light (525 nm, 550 nm) and red light (667 nm) are realized, and under 980 nm excitation, up - converted visible light emission is achieved; Quantum yield improvement: The quantum yield reaches 29%, significantly higher than that of existing lead - free materials (such as 7.68%); Long carrier lifetime: The transient fluorescence lifetime is 1.2 μs, and the density of defect states is low.

[0012] 4. Excellent stability: Under normal temperature and humidity environment for 72 hours, the luminous intensity retention rate ≥ 90%, and for 15 days, the luminous intensity retention rate ≥ 80%.

[0013] 5. Flexible anti - counterfeiting application: Multi - region fluorescent labels are prepared by 3D printing, showing a dynamic color - changing effect under 365 nm / 980 nm excitation, and having strong anti - forgery performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] In order to more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the following will briefly introduce the drawings required for use in the description of the embodiments or the prior art. Obviously, the following drawings are only some embodiments of the present invention. For those of ordinary skill in the art, without creative efforts, other drawings can be obtained based on these drawings, where: Figure 1 is the X - ray diffraction ( XRD )) pattern of samples doped with different rare - earth ions in a rare - earth - ion - doped lead - free halide double perovskite material and its preparation method of the present invention; Figure 2 is the photoluminescence spectrum of a rare - earth - ion - doped lead - free halide double perovskite material and its preparation method of the present invention under 365 nm and 980 nm excitation wavelengths; Figure 3 is for a rare - earth - ion - doped lead - free halide double perovskite material and its preparation method of the present invention scanning electron microscope ( SEM )) image; Figure 4For the undoped and doped Yb3+, Nd3+, Er3+ in a rare-earth ion-doped lead-free halide double perovskite material and its preparation method of the present invention, two different fluorescence decay curves are shown, and the increase in carrier lifetime is used to prove the improvement of carrier transport performance; Figure 5 For the multicolor fluorescence effect of the anti-counterfeiting mark in a rare-earth ion-doped lead-free halide double perovskite material and its preparation method of the present invention; Figure 6 For the stability test chart of a rare-earth ion-doped lead-free halide double perovskite material and its preparation method of the present invention under normal temperature and humidity environment. Detailed implementation manners

[0015] The following combines specific embodiments to detail the implementation details of a rare-earth ion-doped lead-free halide double perovskite material and its preparation method of the present invention, so that those of ordinary skill in the art can implement the present invention.

[0016] Example 1: Material preparation (optimal doping ratio) Please refer to Figures 1 to 4 for a detailed description of the specific implementation process of the rare-earth ion-doped lead-free halide double perovskite material and its preparation method of the present invention: (1) Raw material preparation and weighing Matrix raw materials: Accurately weigh cesium chloride ( , purity ≥ 99.99%, 2 mmol, 0.337 g), sodium chloride ( , purity ≥ 99.99%, 1 mmol, 0.058 g), and gadolinium chloride hexahydrate ( , purity ≥ 99.99%, 0.94 mmol, 0.401 g) using an analytical balance with a precision of 0.0001 g to ensure that the raw materials are free of moisture absorption or impurities.

[0017] Rare-earth dopants: Weigh ytterbium chloride hexahydrate ( , 0.03 mmol, 0.014 g, corresponding to doping concentration of 20 mol%), neodymium chloride hexahydrate ( , 0.005 mmol, 0.002 g, corresponding to doping concentration of 1 mol%), and erbium chloride hexahydrate ( , 0.025 mmol, 0.011 g, corresponding to doping concentration of 5 mol%) according to the optimal doping ratio. The purity of all rare-earth chlorides is ≥ 99.99%.

[0018] Solvent and Acidity Control: Measure 3 mL of hydrochloric acid solution with a concentration of 37 wt% (analytical pure) using a pipette gun and precisely aspirate it. Control the initial pH value of the solution at 1.5 ± 0.2 to inhibit hydrolysis side reactions.

[0019] (2) Mixing and Dispersion Transfer the weighed matrix raw materials ( , , ) and the rare earth dopant ( ) into a 50 mL Teflon liner, and inject 3 mL of hydrochloric acid solution; fix the liner on a magnetic stirrer, set the rotation speed at 500 rpm, and continuously stir for 1 hour until the solution changes from turbid to clear to ensure uniform dispersion of ions.

[0020] (3) Hydrothermal Reaction and Crystal Growth Transfer the mixed solution to a 50 mL stainless steel autoclave, seal it, and place it in a programmable temperature oven. Set the reaction temperature at 180°C ± 2°C and the reaction time at 12 hours ± 0.5 hours; after the reaction is completed, turn off the power of the oven and let the autoclave cool naturally to room temperature (about 25°C) to avoid crystal defects caused by rapid cooling.

[0021] (4) Product Separation and Post-treatment Centrifugal Separation: Transfer the reaction solution to a centrifuge tube and centrifuge it at 12000 rpm for 10 minutes using a high-speed centrifuge. Discard the supernatant and retain the white precipitate at the bottom.

[0022] Washing and Purification: Add 20 mL of absolute ethanol to the precipitate, ultrasonically clean it for 5 minutes, and repeat 3 times until the supernatant is colorless and transparent.

[0023] Drying Treatment: Transfer the precipitate to a vacuum drying oven, set the temperature at 60°C and the vacuum degree at -0.1 MPa, and dry it for 6 hours to finally obtain a white powder product with uniform particle size (200 - 500 nm).

[0024] (5) Material Characterization and Performance Verification X-ray Diffraction ( XRD ) Analysis: The diffraction peaks of the sample are completely matched with the cubic phase standard card (PDF#00 - 001 - 1234), and the lattice parameter a = 10.68 Å, without impurity phase peaks.

[0025] Photoluminescence Spectrum: Under the excitation of 365 nm ultraviolet light, the material emits green light at 525 nm and 550 nm and red light at 667 nm; under the excitation of 980 nm near-infrared light, upconversion visible light emission is achieved.

[0026] Quantum Yield (QY): Tested by the integrating sphere method, when the doping amount is 20 mol%, is 1 mol%, when it is 5 mol%, the quantum yield reaches 29%; by adjusting the doping ratio (such as 15 mol%, 8 mol%), the quantum yield can be increased to 32%, and the lowest value is 25%. The quantum yield is 29%, which is significantly higher than that of existing lead-free perovskite materials.

[0027] Transient fluorescence lifetime: The carrier lifetime is 1.2 μs, indicating a low density of material defect states.

[0028] In Example 1, through orthogonal experiments, it is verified that the total rare earth doping amount ranges from 1 to 50 mol%. When the doping amount exceeds 50 mol%, obvious concentration quenching phenomenon occurs in the material, and the quantum yield drops below 15%; when the doping amount is lower than 1 mol%, the luminescence intensity is insufficient (<50 cd / m²).

[0029] Example 2: Preparation and application of anti-counterfeiting labels Please refer to Figure 5 , and the specific steps are as follows: (1) Preparation of fluorescent slurry Weigh the prepared in Example 1: , Nd³, powder (0.5 g) and polymethyl methacrylate (PMMA, 5.0 g, mass ratio 1:10), add chloroform (10 mL). That is, the mass ratio of the material to PMMA in the fluorescent slurry is 1:10, the dosage of the solvent chloroform is 10 mL, stir magnetically for 30 minutes, and disperse ultrasonically for 30 minutes to form a homogeneous slurry.

[0030] (2) 3D printing template design and preparation Use CAD software to design a template (size: 20 mm × 20 mm × 1 mm) containing a hollowed-out pattern "CJLU", a border, and a background area. Use a Formlabs Form 3B stereolithography 3D printer (ultraviolet light wavelength 405 nm, power 250 mW) with transparent resin as the raw material, set the layer thickness to 0.1 mm and the filling density to 80%. After printing, clean with isopropyl alcohol and cure with ultraviolet light. The wavelength 405 nm of this equipment matches the upconversion luminescence characteristics of the material to ensure the precise formation of the fluorescent pattern.

[0031] (3) Filling of fluorescent slurry and label forming Partition filling: Use a micro syringe to inject different fluorescent slurries into the template areas: fill the text area with single-doped slurry (5 mol%), corresponding to green light; fill the border area with single-doped slurry (1 mol%), corresponding to red light; fill the background area with Single-doped slurry (20 mol%), corresponding to yellow light.

[0032] Drying and demolding: After drying at room temperature for 24 hours, the template was peeled off to obtain multicolor fluorescent labels.

[0033] (4) Anti-counterfeiting performance test Multi-wavelength excitation response: Under 365 nm ultraviolet light excitation, the text shows green fluorescence; under 980 nm near-infrared light excitation, the background shows yellow fluorescence.

[0034] Example 3: Stability verification Please refer to Figure 6 , and the materials of Example 1 were placed in an environment of normal temperature and humidity for testing: Under normal temperature and humidity environment for 72 hours, the luminous intensity retention rate ≥ 90%, and the luminous intensity retention rate after 15 days ≥ 80%.

[0035] A rare earth ion-doped lead-free halide double perovskite material and its preparation method according to the present invention have the following remarkable advantages compared with the prior art: 1. Lead-free environmental protection: Using the matrix to replace the traditional lead-based perovskite, completely eliminating lead toxicity and meeting the requirements of green environmental protection.

[0036] 2. Controllable synthesis process: The hydrothermal synthesis conditions are mild (180 °C, 12 h), the product has high crystallinity and uniform particle size (200 - 500 nm), and the doping ratio is accurately controllable ( 1 - 30%, 1 - 10%, 1 - 20%).

[0037] 3. Excellent optical properties: Dual-mode luminescence: Down-conversion green light (525 nm, 550 nm) and red light (667 nm) are achieved under 365 nm excitation, and up-conversion visible light emission is achieved under 980 nm excitation; Quantum yield improvement: The quantum yield reaches 29%, significantly higher than that of existing lead-free materials (such as 7.68%); Long carrier lifetime: The transient fluorescence lifetime is 1.2 μs, and the defect state density is low.

[0038] 4. Excellent stability: Under normal temperature and humidity environment for 72 hours, the luminous intensity retention rate ≥ 90%, and the luminous intensity retention rate after 15 days ≥ 80%.

[0039] 5. Flexible anti-counterfeiting application: Multi-region fluorescent labels are prepared by 3D printing, showing a dynamic color-changing effect under 365 nm / 980 nm excitation, and having strong anti-counterfeiting performance.

[0040] Although the specific embodiments of the present invention have been described above, those skilled in the art should understand that these specific embodiments are merely illustrative. Without departing from the principle and essence of the present invention, those skilled in the art can make various omissions, substitutions, and changes to the details of the above methods and systems. For example, combining the above method steps so as to perform substantially the same function in a substantially the same way to achieve substantially the same result falls within the scope of the present invention. Therefore, the scope of the present invention is only defined by the appended claims.

Claims

1. A rare earth ion doped lead-free halide double perovskite material, characterized in that: Its chemical formula is ,in The doping concentration is 1-30mol%, The doping concentration is 1-10mol%. The doping concentration is 1-20mol%, and the total rare earth ion doping amount accounts for 1-50 mol% of the site.

2. The rare earth ion doped lead-free halide double perovskite material according to claim 1, characterized in that: Said , , The doping concentrations are 20 mol%, 1 mol% and 5 mol% respectively.

3. The rare earth ion doped lead-free halide double perovskite material according to claim 1, characterized in that: The material emits green light (525nm, 550nm) and red light (667nm) under the excitation of 365nm ultraviolet light, and achieves up-conversion visible light emission under the excitation of 980nm near-infrared light, with a quantum yield of 25-32%.

4. The rare earth ion doped lead-free halide double perovskite material according to claim 1, characterized in that: After the material is exposed to a normal temperature and humidity environment for 72 hours, the luminous intensity retention rate is ≥90%.

5. A method for preparing a rare earth ion-doped lead-free halide double perovskite material according to any one of claims 1 to 4, characterized in that: The following steps are involved: (1) Weigh in a molar ratio of 2:1:1 , , , with rare earth chlorides , , Mixed, the total rare earth ion amount is 1mmol; (2) The mixture was dissolved in 3 mL 37 wt% hydrochloric acid solution and magnetically stirred for 1 hour; (3) The mixed solution was transferred to a 50 mL Teflon reactor, sealed and placed in an oven at 180 °C for 12 hours; (4) Cool naturally to room temperature, separate the precipitate by centrifugation, wash three times with anhydrous ethanol, and dry under vacuum at 60°C for 6 hours to obtain the target product.

6. The method for preparing a rare earth ion-doped lead-free halide double perovskite material according to claim 5, characterized in that: The purity of the rare earth chloride is ≥99.99%, and the pH value of the solution is controlled at 1-3 before the reaction.

7. Use of a rare earth ion doped lead-free halide double perovskite material in an anti-counterfeiting mark according to any one of claims 1 to 4, characterized in that: The following steps are involved: (1) mixing the material with the polymer matrix in a mass ratio of 1:5-1:15 and dissolving in an organic solvent to form a fluorescent slurry; (2) Using 3D printing technology to prepare a template with a hollow pattern, and filling the fluorescent slurry into different areas; (3) After drying, an anti-counterfeiting mark is obtained, which displays dynamic multi-color fluorescence under excitation at 365 nm and 980 nm.

8. The use of a rare earth ion doped lead-free halide double perovskite material in an anti-counterfeiting mark according to claim 7, characterized in that: The polymer matrix is ​​polymethyl methacrylate (PMMA) or polycarbonate (PC), and the organic solvent is chloroform or tetrahydrofuran.

9. The use of a rare earth ion doped lead-free halide double perovskite material in an anti-counterfeiting mark according to claim 7, characterized in that: The anti-counterfeiting mark has a luminous intensity retention rate of ≥90% for 72 hours and a luminous intensity retention rate of ≥80% for 15 days under normal temperature and humidity conditions.

Citation Information

Patent Citations

  • Er &lt; 3 + &gt;-doped rare earth-based double perovskite single crystal and preparation method and application thereof

    CN115028184A